The neurons, the butterflies of the soul - Canchola Martínez, Enrique (2021)
Brain butterflies (neurons) with their flutter create the emotions, feelings, memories, ideas, memory, reasoning, spirituality, consciousness and subjective experience that synchronize man with the universe.